Gastric intramucosal pH: a predictor of survival in cardiac surgery patients with low cardiac output? - Böhrer, Hubert; Schmidt, Heinfried; Motsch, Johann; Gust, René; Bach, Alfons; Martin, Eike (Journal of cardiothoracic and vascular anesthesia, 1997)
Objective: To assess the value of gastric intramucosal pH measurement in patients with low output after cardiac surgery. Design: Prospective clinical study. Setting: University hospital. Participants: Fifteen patients with low output after cardiac surgery were included. Those who survived the first postoperative day (n = 14) remained in the study. Interventions: Gastric intramucosal pH and arterial lactate concentrations were measured 6, 12, and 24 hours after admission to the intensive care unit. Intravenous infusion of buffer solutions was strictly avoided during the equilibration period and in the half hour before injection of saline into the gastric balloon of the tonometer. Measurements and Main Results: Eight patients survived during the 28-day observation period, and six patients died. On admission to the intensive care unit, no difference in cardiac index (1.56 v 1.54 L/min/m2) or pulmonary capillary wedge pressure (17.3 v 17.7 mmHg) was found between survivors and nonsurvivors. During the first 24 hours after surgery, arterial lactate was significantly higher in the nonsurvivor group (61 v 23 mg/dL), but there was no difference between the gastric intramucosal pH of survivors and nonsurvivors (7.41 v 7.42 on admission). Conclusions: Calculated gastric mucosal pH is not an early predictor of survival in cardiac surgery patients with postoperative low cardiac output syndrome. Further studies are required to assess whether the gradient between arterial and intramucosal partial pressure of carbon dioxide (Pco2) might be a more useful predictive value.